FOREIGN LANGUAGE PROFICIENCY AND STUDY SKILLS AMONG INDONESIAN AND THAI GRADUATE STUDENTS OF EDUCATION STUDIES - Setiadi, Riswanda; Pirakun, Araya (UPI Press, 2015)
The research was aimed at identifying Indonesian and Thai graduate students’ competence in foreign language, English or other foreign languages, describing their study skills by documenting their foreign language learning strategies, and documenting the ways in which they use their competence in English or other foreign languages to facilitate their learning processes. Participants of the study possessed different foreign language skills other than English. Some Indonesian students could speak French and Japanese, and Thai students were able to speak Chinese and Laos. However, their foreign language skills were mostly poor. Only a few students claimed that they were good foreign language speakers. It is believed that when individuals do not practice their foreign language skills frequently, they will lose their skills acquisition as they are not able to keep their language knowledge in their memory. In terms of language use, they speak foreign language(s) for academic, professional, economic, and cultural purposes. In sum, both Indonesian and Thai graduate students are mostly classified into receptive type of learners as they tend to improve receptive language skills rather than productive ones because for their academic purposes, which only require them to read and listen. It is recommended that the students improve their academic writing skills.